Antibiotic resistance patterns and plasmids in Leuconostoc oenos - Janse, B. J. H.(Bernard Johannes Heinrich) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1987.